System of exercises for grammar presentation and consolidation communicatively - Горбушина, Т.Ю. (My University, 2016)
The main goal of this work is to help students to avoid grammar mistakes in the process of speaking i.e. to form grammar skills through communication. Grammar it is the sphere that teachers find difficult to teach and the student find it difficult to learn, especially to use it in communication. That is why we need to pay more attention to the question of teaching grammar communicatively.
Keywords: grammar; communicative approach; system of exercises